Application and Prospects of Hydrogel Additive Manufacturing - Changlong Zhao; Qiyin Lv; Wenzheng Wu (Gels, 2022)
Hydrogel has become a commonly used material for 3D and 4D printing due to its favorable biocompatibility and low cost. Additive manufacturing, also known as 3D printing, was originally referred to as rapid prototyping manufacturing. Variable-feature rapid prototyping technology, also known as 4D printing, is a combination of materials, mathematics, and additives. This study constitutes a literature review to address hydrogel-based additive manufacturing technologies, introducing the characteristics of commonly used 3D printing hydrogel methods, such as direct ink writing, fused deposition modeling, and stereolithography. With this review, we also investigated the stimulus types, as well as the advantages and disadvantages of various stimulus-responsive hydrogels in smart hydrogels; non-responsive hydrogels; and various applications of additive manufacturing hydrogels, such as neural catheter preparation and drug delivery. The opportunities, challenges, and future prospects of hydrogel additive manufacturing technologies are discussed.